Zakat Distribution to Reach the Most Vulnerable Communities in Padangsidimpuan City: Perspective of Maqāṣid al-Sharī‘ah Al-Syāṭibī - Harahap, Purnama Hidayah; Ridwan, Muhammad; Hasanah, Uswatun (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2025)
In the perspective of Maqāṣid al-Sharī'ah according to Al-Syāṭibī, zakat plays a central role in realizing the benefits of the ummah (jalb al-maṣāliḥ) and preventing harm (dar' al-mafāsid). However, the practice of distributing zakat in Padangsidimpuan City still faces various obstacles, such as limited mustachik data, long bureaucracy, and geographical barriers, so that the benefits of zakat are not optimal for vulnerable groups. Along with the development of technology, various innovations have begun to be implemented to increase the effectiveness, transparency, and accountability of zakat distribution. This study uses a qualitative method with a descriptive-analytical approach to analyze the role of zakat distribution innovation in increasing accessibility and efficiency in accordance with Maqāṣid al-Sharī'ah. Data was collected through observations, in-depth interviews with zakat institutions, and focused group discussions with beneficiaries and stakeholders. The results of the study show that the use of technology, such as digital zakat platforms, mustahik identification systems, and mobile-based disbursement, significantly increases the accessibility, efficiency, and transparency of zakat distribution. These findings reflect efforts to protect property (ḥifẓ al-māl), and are reinforced by community-based participatory models and collaboration of local stakeholders that support the sustainability and accountability of zakat management.